To what extent does a Christian husband have the right to have several wives - Hakam El Khon, Mahmoud Abd El (Opción, 2019)
The study aims to investigate whether a Christian husband has the right to have several wives via a mixed methodology that combines the deep consideration of the background of the hypothesis of the research and the analytical approach. As a result, for a Christian husband to have more than one wife at the same time even if they are followers of different sects or doctrines is groundless. In conclusion, the principles of Islamic Sharia Law shall apply under the above-mentioned assumption then a Christian husband shall enjoy the same rights as a Muslim husband.